Development of Comic Mathematics Teaching Materials on Flat-Building Material to Increase Reading Interest in Class IV Elementary School Students - Yuniarti, Anggita; Radia, Elvira Hoesein (Journal of Education Technology, 2020)
The problem of the student’s low reading interest is the variety of learning media in delivering material. The lack of reading interest that students have about books provided by schools is less attractive. Research aims to develop the raw materials of comics in flat waking materials to increase interest in reading elementary school students. Research and development carried out are four steps, namely: definition, design, development, and propagation. The analysis process collects qualitative and quantitative data from materials experts, design experts, the specific educators in math subjects, and class iv student participants using the likert scale. Based on the validity of expert media and material experts obtained from a first validity test with an 83.3% rating categorized perfectly worthy of use, a second validity test with an average of 90% is categorized perfectly worthy of use and an 80% is categorized asa learning medium. The development of comics for mathematical materials in flat waking materials to increase interest in reading the fourth graders is worth using and can serve asa guide in learning.